Penggunaan Media Boards Games untuk Meningkatkan Kemampuan Menulis Opini dan tanggapan Siswa kelas V - Putu Eka Mega Jayanti; Ni Putu Chandra Dewi Swandari; Ni Nyoman Kurnia Wati; I Nyoman Raka (Indonesian Journal Publisher, 2026)
This study aims to analyze the effectiveness of board games as an instructional medium in improving fifth-grade elementary students’ opinion and response writing skills. The research is motivated by the low ability of students to develop ideas, construct logical arguments, and organize their writing coherently. This study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Data were collected from reputable databases, including Google Scholar, DOAJ, SINTA, ERIC, and ProQuest, focusing on publications from 2020 to 2025. Out of 243 identified articles, 30 met the inclusion criteria and were analyzed thematically. The analysis focused on the contribution of board games to the development of critical thinking skills, argumentation ability, vocabulary enrichment, learning motivation, and overall writing quality. The findings indicate that board games consistently enhance students’ active engagement through social interaction, discussion, and decision-making processes that support idea construction before being expressed in written form. Furthermore, game-based learning creates an enjoyable classroom atmosphere, which increases students’ confidence and interest in writing activities. Although challenges such as time management and teacher readiness were identified, board games demonstrate significant potential as an innovative instructional medium for strengthening productive literacy skills at the elementary level. Therefore, integrating board games into Indonesian language instruction is recommended as an effective and contextual teaching strategy